The development of Franchise fast food restaurant in Malaysia : the views of consumer on Kuching market - Zakaria, bin Ibrahim. (2004)
This study would attempt to scrutinize the development of franchise fast food restaurant business in Malaysia after 10 years inception of the Franchise development program in 1992. This study would also attempt to analyze the views of consumers on the franchise fast food restaurant business on Kuching city